Gender equality on developing transport system in sicily: A consideration on regional scale - Campisi T.; Nahiduzzaman Kh.Md.; Akgün, Nurten; Ticali D.; Tesoriere G. (American Institute of Physics Inc., 2021)
The development of transport technologies and systems, taking into account individual and/or shared mobility systems, should involve not only the characteristics of the places where it develops, but also the characteristics of road users. The increase in transport supply makes it easier to achieve job opportunities and thus increases the potential for wealth. The development of different forms of mobility also offers better access to areas, such as education centers, and limits the disparity between road users of different age groups and gender. The presence of children and income characteristics are factors that can influence women's mobility choice such as using public transport, owned/shared micro mobility, or e-bikes. The study in this paper defines in a first phase some considerations on gender equality through describing some case studies from the South of the world. A questionnaire, including 1150 women over 18 years old in the use of the different modes of transport in the region of Sicily in southern Italy, was carried out. The results highlight the critical issues that often lead to different perceptions of safety on board or gender equality considering both the passenger's and the driver's point of view. The limits of the research are related to the analyzed sample. The work shows a first step of investigation aimed at future research actions to reduce gender inequalities, providing the basis for the definition of ad hoc strategies by local authorities and dedicated vouchers or fares by operators of transport services for women.
International Conference of Computational Methods in Sciences and Engineering 2020, ICCMSE 2020
Keywords: Descriptive statistics; Gender equality; Mobility choices